PENGARUH INOVASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN KAOS MEREK JAKOZ - Fansuri, Faisal (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
This study aims to determine the effect of a variable products innovation consisting of sub-variables relative advantage, compatibility, complexity, divisibility, and communicability on purchasing decisions on a T-shirt & Souvenir Jakoz outlets in the city of Jambi. This research is a survey using a questionnaire instrument. The samples used were 100 consumer brands Jakoz shirts. The analytical tool used is multiple linear regression analysis. This study indicates that product innovation (relative advantage, compatibility, complexity, divisibility, and communicability) simultaneously influences consumer purchasing decisions in partial compatibility, complexity, divisibility, and communicability influence purchase decisions. In contrast, the relative superiority does not affect the purchase decisions on Jakoz shirt brand products in Jambi.